Collateral Damage The Influence of Political Rhetoric on the Incorporation of Second-Generation Americans - Richey, Sean (University of Michigan Press, 2023)
Collateral Damage provides an overview of how political communication influences the process of incorporation with the broad society as well as its political parties. Sean Richey shows that how politicians talk about immigrants affects how their children perceive America and their feelings about the nation. These perceptions and feelings in turn greatly influence the children's desire to incorporate into American political society. He also shows that regardless of a speaker's intended outcome, what is said can still have a deleterious effect on incorporation desire, a communicative process that he terms "collateral damage." Richey uses new experimental and survey evidence, as well as the rhetoric of Donald Trump as a test case, to examine how anti-immigration communication influences the incorporation of the children of immigrants.